2017
DOI: 10.2147/jaa.s140577
|View full text |Cite
|
Sign up to set email alerts
|

The evolving role of tiotropium in asthma

Abstract: Tiotropium is a long-acting muscarinic antagonist (LAMA) that exerts its bronchodilatory effect by blocking endogenous acetylcholine receptors in the airways. Its safety and efficacy are well established for the treatment of COPD, and it is now being recognized for its role in improving lung function and control in asthma. This review discusses the evolving role of tiotropium delivered by the Respimat® in patients across the range of asthma severities and ages, and provides an overview of safety and efficacy d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Consequently, in the past decade, various steps have been taken to improve the quality of life of asthma patients. These include: implementation of laws banning smoking in public spaces [19, 20], introducing new treatments such as monoclonal antibody-based therapies [21], and guideline-recommended new indication of LAMAs [22] for the effective treatment of patients with asthma. After a decade, our results show that patients with asthma still have a poor quality of life and experience symptoms that affect their daily lives.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, in the past decade, various steps have been taken to improve the quality of life of asthma patients. These include: implementation of laws banning smoking in public spaces [19, 20], introducing new treatments such as monoclonal antibody-based therapies [21], and guideline-recommended new indication of LAMAs [22] for the effective treatment of patients with asthma. After a decade, our results show that patients with asthma still have a poor quality of life and experience symptoms that affect their daily lives.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive Phase III study programme detailed below, and summarized in Table 1 [ 20 ], has demonstrated the safety and efficacy of tiotropium in adult patients with mild, moderate, and severe asthma. The majority of the Phase III trials have evaluated tiotropium in the Respimat form, with the Tiotropium Bromide as an Alternative to Increased Inhaled Corticosteroid in Patients Inadequately Controlled on a Lower Dose of Inhaled Corticosteroid study (TALC Study, NCT00565266) being one of the exceptions.…”
Section: Tiotropium In Asthma: the Evidence Basementioning
confidence: 99%
“…In both studies, tiotropium Respimat was well tolerated with comparable adverse event rates across treatment and placebo groups [ 37 , 38 ]. There are further five Phase III clinical trial studies in the paediatric population ( Table 2 [ 20 ]), which are discussed in detail below.…”
Section: Patient Selection and Safety Considerationsmentioning
confidence: 99%
See 2 more Smart Citations